Advertisements and Sexism in the Philippines - Sales, April Jane G.; Leuterio, Glarissa D.; Lopez, Lurie Jane S.; Matinao, Claire Dianne G.; Naces, Lorna C.; Ramos, Ariel L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Advertisements have been an effective tool used to promote a product or service. It can also be considered as a way to shape the mind and the culture of society. Hence, this study determined the linguistic elements and analyzed different types of sexism through language in Philippine television advertisements. The study used qualitative approach to research and utilized a validated self-made research instrument which served as the primary tool of the study. The study identified the linguistic elements present in Philippine television advertisements in terms of its lexical and syntactical feature and analyzed the types of sexism through language in Philippine advertisements. The study revealed that the commonly used lexical feature of advertisements is simple vocabulary; meanwhile for syntactic feature, the most common is ambiguity and the use of imperative. It is also found that advertisements can be used as a sexism platform in the Philippines. Moreover, the way these elements are used or depicted along with the portrayal of men and women in the advertisements may influence the audience’s perception and understanding of what they have seen thus, the audio-video material as output of this study may serve as a tool to liberate the minds of the viewing public.